2021
DOI: 10.1073/pnas.2019208118
|View full text |Cite
|
Sign up to set email alerts
|

Dead clades walking are a pervasive macroevolutionary pattern

Abstract: D. Jablonski [Proc. Natl. Acad. Sci. U.S.A. 99, 8139–8144 (2002)] coined the term “dead clades walking” (DCWs) to describe marine fossil orders that experience significant drops in genus richness during mass extinction events and never rediversify to previous levels. This phenomenon is generally interpreted as further evidence that the macroevolutionary consequences of mass extinctions can continue well past the formal boundary. It is unclear, however, exactly how long DCWs are expected to persist after extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
(56 reference statements)
3
15
0
Order By: Relevance
“…Instead, the record of evolution gets decimated together with, or within a short time from, topography-reshaping TREs. This reasoning agrees with the find that most species continue after an extinction event for more than 30 My, while many post-event drops in diversity without recovery are not associated with mass extinction events at all (Barnes et al, 2021). Similarly, pre-Milankovitch views that climate periodicity is due to changes in Earth's magnetic field (Puetz et al, 2016, Raup, 1985 made sense only due to the geomagnetism record's dominant bias in the same way.…”
Section: Extraction Of Previously Reported Periods Of Cratering and Extinctionssupporting
confidence: 85%
See 1 more Smart Citation
“…Instead, the record of evolution gets decimated together with, or within a short time from, topography-reshaping TREs. This reasoning agrees with the find that most species continue after an extinction event for more than 30 My, while many post-event drops in diversity without recovery are not associated with mass extinction events at all (Barnes et al, 2021). Similarly, pre-Milankovitch views that climate periodicity is due to changes in Earth's magnetic field (Puetz et al, 2016, Raup, 1985 made sense only due to the geomagnetism record's dominant bias in the same way.…”
Section: Extraction Of Previously Reported Periods Of Cratering and Extinctionssupporting
confidence: 85%
“…The 10-My bin is a gauge best-fitting the overlap intervals, averaging the time for which most species continue after an extinction event (cf. Barnes et al, 2021, who found that most species continue for more than 30 My, while many drops in diversity without recovery are not associated with mass extinction events at all). Dashed arc depicts a period (wave) as it rolls out in the time domain.…”
Section: Extraction Of Previously Reported Periods Of Cratering and Extinctionsmentioning
confidence: 99%
“…Our results show that both the taxonomic diversity and morphological disparity dropped dramatically during the Early Triassic ( Figures 2 and 4 ). Combined with the phylogenetic results ( Figure 3 ), our suite of analyses yields a clear ecological signal from beetles across the Permian/Triassic boundary: all xylophagous stem-group beetles become extinct near the Permian-Triassic boundary or abruptly decreased in the Early Triassic (a pattern called ‘dead clade walking’; Barnes et al, 2021 ), while aquatic phoroschizid and ademosynid lineages crossed the Permian/Triassic boundary and diversified in the Middle Triassic. Coleoptera recovered in taxonomic diversity during the Middle Triassic by the rise of new predatory and herbivorous groups, synchronized with the recovery of terrestrial ecosystems ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 58%
“…We do not investigate the effect of mass extinctions or varying rates of speciation and extinction which may better explain the timetree of life (12). If molecular clock estimates did exceed the expectations of this null model, an alternative model would have to be invoked to explain the findings [e.g., (29,30)]. However, the results of our simulations indicate that this is not currently necessary and that the molecular evidence and null expectations of tree shape are not in disagreement.…”
Section: Implications For Interpreting the Fossil Record And The Vera...mentioning
confidence: 99%